Key-determinants of knowledge sharing culture on job performance and moderating role of job position: a study in Majlis Bandaraya Shah Alam (MBSA) / Farah Wahida Mohamad Rafly - Mohamad Rafly, Farah Wahida (2018)
Currently, the practice of knowledge sharing has become a key factor in gaining and producing better knowledge among most of the Malaysians including public servants. Knowledge sharing culture is believed to be a very important culture that needs to be developed and implemented in every organization in public sector in Malaysia in order to achieve better job performance. This research was based on data obtained from a survey questionnaire and several questions from interviews with randomly selected interviewees. The data was analyzed to evaluate and determine the relationships of the key-determinants of knowledge sharing culture and job performance in Majlis Bandaraya Shah Alam (MBSA).